A method for treating the inner copper surface of a printed circuit board
Through the treatment of anodizing and silane coupling agent, the problem of increased conductor loss after copper foil surface treatment is solved, which significantly reduces the loss of high-frequency signals and improves signal integrity.
Patent Information
- Application Number
- CN202211615035.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-12-14
AI Technical Summary
In the prior art, the copper foil surface treatment leads to an increase in conductor loss of signal transmission, affecting the integrity of high-frequency transmission signals.
Anodized and silane coupling agent treatment methods are used to oxidize the copper foil through a specific surface treatment process, including the use of anodized liquid composed of sodium hydroxide, organic acid salts, EDTA and copper ions, followed by silane coupling agent treatment. , combined with pickling, degreasing, ultrasonic cleaning and drying steps, optimize current density and temperature control to reduce conductor losses.
It significantly reduces the conductor loss of signal transmission and improves the integrity of high-frequency signals, especially under 16GHz signals, which show obvious advantages over commercially available processing methods.
Smart Images

Figure CN115747913B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal surface treatment, and in particular to a method for treating the inner copper surface of a printed circuit board. Background Art
[0002] At present, printed circuit boards, as important components of the electronics industry, are widely used in various electronic devices due to their advantages such as good assembly, high reliability, strong productivity, and high density. With the rapid development and widespread application of integrated circuits, printed circuit boards are constantly being updated, from single-sided boards to double-sided boards, multi-layer boards and flexible boards, and the density of components is constantly increasing. In order to ensure the quality of printed circuit boards and improve working reliability, it is very important to ensure a firm bond between layers. The surface of the copper foil is smooth, and the surface of the copper foil needs to be treated accordingly to improve the bonding strength between the layers so as to ensure a firm bond between the layers and avoid the phenomenon of delamination and explosion.
[0003] For example, CN104099652A discloses a surface treatment roughening process for electronic copper foil, the steps of which are as follows: cathode copper and concentrated sulfuric acid are mixed and dissolved to prepare a roughening solution; wherein Cu 2+ :20-40g / L, H2SO4:80-150g / L, the roughening solution temperature is 25-40℃; the obtained roughening solution is mixed fully and then enters the roughening tank, and electroplating is carried out in turn at high current density, medium current density and low current density. The roughening process adopted by the present invention uses one electroplating solution to replace the roughening solution and curing solution of two different components, and realizes the electrolytic copper foil with high specific surface area, low peak value and high bonding force by controlling different current densities, and has excellent peel strength when applied to Tg170 and above plates.
[0004] CN113973437A discloses a surface treatment method for copper foil for high-speed high-frequency signal transmission circuit boards, which provides a raw copper foil with low profile and meets the requirements of anti-peeling performance for printed circuit boards for high-speed high-frequency signals, and provides a copper foil that does not contain ferromagnetic metal elements and has excellent PIM performance for 5G communication. The method includes: adding a dispersant and nano-alumina particles to a copper-containing electrolytic solution, mixing them fully, and electrochemically co-depositing on the surface of the copper foil to form a metal composite deposition layer with a high specific surface area structure. Electroplating a copper layer, a zinc layer and a chromium layer on the composite layer in turn, and then applying a silane coupling agent to form a complete treatment layer. The treatment layer has the characteristics of small thickness, large specific surface area, low roughness and high anti-peeling strength. The process is simple, can meet the passive intermodulation PIM function of high-frequency and high-speed signals, and has considerable application prospects in the field of 5G high-frequency and high-speed communications.
[0005] However, the copper foil obtained in the prior art will increase the conductor loss of signal transmission after surface treatment, which is affected by the skin effect, especially the integrity of high-frequency transmission signals. As the frequency of communication transmission continues to increase, printed circuit boards tend to be high-frequency and high-speed, and the requirements for signal transmission integrity at high frequencies continue to increase, which puts forward new requirements for the existing inner copper foil surface treatment process. It is necessary to optimize the existing process or explore new process methods to ensure that the interlayer bonding is firm and reduce the impact of conductor loss on signal integrity. Summary of the invention
[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for treating the inner copper surface of a printed circuit board to solve the problem that after the surface treatment of the copper foil, the conductor loss of signal transmission increases and the integrity of the high-frequency transmission signal is greatly affected.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] The present invention provides a method for treating the inner copper surface of a printed circuit board, the method comprising:
[0009] The copper foil is subjected to anodizing and silane coupling agent treatment in sequence;
[0010] The anodizing solution comprises sodium hydroxide, organic acid salt, EDTA and copper ions.
[0011] The surface treatment method provided by the present invention adopts a specific surface treatment process, so that the treated copper foil avoids the problems of increased conductor loss in signal transmission and a significant impact on the integrity of high-frequency transmission signals, and significantly reduces the impact of conductor loss on signal integrity.
[0012] In the present invention, the organic acid salt can be aminocarboxylate, hydroxycarboxylate, organic phosphonate, etc., such as potassium sodium tartrate, sodium ethylenediaminetetramethylenephosphate, amine trimethylenephosphate, diethylenetriaminepentacarboxylate or heptanoate, etc.
[0013] In the present invention, the copper foil is sequentially pickled, degreased and ultrasonically cleaned before anodizing. The pickling is performed by using dilute sulfuric acid for cleaning, and the degreasing is performed by using a mixed solution of sodium hydroxide and sodium carbonate for cleaning the copper foil.
[0014] In the present invention, the anode in the anodic oxidation is the copper foil of the present invention, and the cathode is a graphite sheet, and the two have the same area.
[0015] In the present invention, cleaning and drying are performed before anodizing and silane coupling agent treatment. The cleaning is performed by using water or ethanol to remove the residual anodizing liquid on the surface, and then drying is performed at 120-130° C. for 3-60 minutes.
[0016] In the present invention, the silane coupling agent treatment is followed by cleaning and drying, wherein the cleaning is performed with water or ethanol to remove the residual anodic oxidation liquid on the surface, and then the surface is dried at 120-130° C. for 3-60 minutes.
[0017] In the present invention, the treatment liquid in the silane coupling agent treatment is a water-alcohol solution containing a silane coupling agent, that is, the solutes are water and ethanol, and the specific ratio can be adjusted according to the prior art.
[0018] As a preferred technical solution of the present invention, the sodium hydroxide concentration in the anodizing solution is 5-10 mol / L, the organic acid salt concentration is 0.1-0.6 mol / L, the EDTA concentration is 0.1-0.3 mol / L, and the copper ion concentration is 0.01-0.05 mol / L.
[0019] In the present invention, the concentration of sodium hydroxide in the anodizing solution is 5-10 mol / L, for example, it can be 5 mol / L, 5.5 mol / L, 6 mol / L, 6.5 mol / L, 7 mol / L, 7.5 mol / L, 8 mol / L, 8.5 mol / L, 9 mol / L, 9.5 mol / L or 10 mol / L, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0020] In the present invention, the concentration of the organic acid salt in the anodizing solution is 0.1-0.6 mol / L, for example, 0.1 mol / L, 0.12 mol / L, 0.14 mol / L, 0.16 mol / L, 0.18 mol / L, 0.2 mol / L, 0.22 mol / L, 0.24 mol / L, 0.26 mol / L, 0.28 mol / L, 0.3 mol / L, 0.32 mol / L, 0.34 mol / L. ol / L, 0.36mol / L, 0.38mol / L, 0.4mol / L, 0.42mol / L, 0.44mol / L, 0.46mol / L, 0.48mol / L, 0.5mol / L, 0.52mol / L, 0.54mol / L, 0.56mol / L, 0.58mol / L or 0.6mol / L, but not limited to the listed values, and other unlisted values within the range are equally applicable.
[0021] In the present invention, the concentration of EDTA in the anodizing solution is 0.1-0.3 mol / L, for example, it can be 0.1 mol / L, 0.11 mol / L, 0.12 mol / L, 0.13 mol / L, 0.14 mol / L, 0.15 mol / L, 0.16 mol / L, 0.17 mol / L, 0.18 mol / L, 0.19 mol / L, 0.2 mol / L, 0.21 mol / L, 0.22 mol / L, 0.23 mol / L, 0.24 mol / L, 0.25 mol / L, 0.26 mol / L, 0.27 mol / L, 0.28 mol / L, 0.29 mol / L or 0.3 mol / L, etc., but is not limited to the listed values, and other unlisted values within this range are equally applicable.
[0022] In the present invention, the concentration of copper ions in the anodizing solution is 0.01-0.05 mol / L, for example, it can be 0.01 mol / L, 0.015 mol / L, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L, 0.035 mol / L, 0.04 mol / L, 0.045 mol / L or 0.05 mol / L, but is not limited to the listed values, and other unlisted values within this range are equally applicable.
[0023] As a preferred technical solution of the present invention, the anodizing time is 2-10min, for example, it can be 2min, 2.2min, 2.4min, 2.6min, 2.8min, 3min, 3.2min, 3.4min, 3.6min, 3.8min, 4min, 4.2min, 4.4min, 4.6min, 4.8min, 5min, 5.2min, 5.4min, 5.6min, 5.8min, 6min, 6.2min, 6.4min, 6.6min, 6.8min, 7min, 7.2min, 7.4min, 7.6min, 7.8min, 8min, 8.2min, 8.4min, 8.6min, 8.8min, 9min, 9.2min, 9.4min, 9.6min, 9.8min or 10min, etc., but is not limited to the listed values, and other unlisted values within the range are equally applicable.
[0024] As a preferred technical solution of the present invention, the temperature of the anodizing is 30-50°C, for example, it can be 30°C, 30.5°C, 31°C, 31.5°C, 32°C, 32.5°C, 33°C, 33.5°C, 34°C, 34.5°C, 35°C, 35.5°C, 36°C, 36.5°C, 37°C, 37.5°C, 38°C, 38.5°C, 39°C, 39.5°C or 40°C, etc., but is not limited to the listed values, and other unlisted values within the range are equally applicable.
[0025] As a preferred technical solution of the present invention, the current density of the anodic oxidation is 5-30 mA / cm 2 , for example, it can be 5mA / cm 2 , 6mA / cm 2 , 8mA / cm 2 , 10mA / cm 2 , 12mA / cm 2 , 14mA / cm 2 , 16mA / cm 2 , 18mA / cm 2 , 20mA / cm 2 , 22mA / cm 2 , 24mA / cm 2 , 26mA / cm 2 or 28mA / cm 2 or 30mA / cm 2 The above values are not limited to the above values, and other values not listed in the above values are also applicable.
[0026] As a preferred technical solution of the present invention, the silane coupling agent used in the silane coupling agent treatment includes one or a combination of at least two of vinyl trichlorosilane, 3-aminopropyl triethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy), γ-chloropropyl-trimethoxysilane or γ-methacryloxypropyl-trimethoxysilane.
[0027] In the present invention, the combination of silane coupling agents can be a combination of vinyl trichlorosilane and vinyl triethoxysilane, a combination of vinyl tri(β-methoxyethoxy) and γ-chloropropyl-trimethoxysilane, or a combination of vinyl triethoxysilane and vinyl tri(β-methoxyethoxy), but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0028] As a preferred technical solution of the present invention, the mass concentration of the silane coupling agent in the treatment solution used in the silane coupling agent treatment is 10-15%, for example, it can be 10%, 10.2%, 10.4%, 10.6%, 10.8%, 11%, 11.2%, 11.4%, 11.6%, 11.8%, 12%, 12.2%, 12.4%, 12.6%, 12.8%, 13%, 13.2%, 13.4%, 13.6%, 13.8%, 14%, 14.2%, 14.4%, 14.6%, 14.8% or 15%, etc., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0029] As a preferred technical solution of the present invention, the temperature of the treatment liquid used in the silane coupling agent treatment is 30-60°C, for example, it can be 30°C, 32°C, 34°C, 36°C, 38°C, 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C or 60°C, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0030] As a preferred technical solution of the present invention, the treatment time of the silane coupling agent is 10-15min, for example, it can be 10min, 10.2min, 10.4min, 10.6min, 10.8min, 11min, 11.2min, 11.4min, 11.6min, 11.8min, 12min, 12.4min, 12.6min, 12.8min, 13min, 13.2min, 13.4min, 13.6min, 13.8min, 14min, 14.2min, 14.4min, 14.6min, 14.8min or 15min, but is not limited to the listed values, and other unlisted values within the range are equally applicable.
[0031] As a preferred technical solution of the present invention, the treatment method comprises: performing anodizing and silane coupling agent treatment on the copper foil in sequence;
[0032] The anodic oxidation solution comprises sodium hydroxide, organic acid salt, EDTA and copper ions; the sodium hydroxide concentration in the anodic oxidation solution is 5-10 mol / L, the organic acid salt concentration is 0.1-0.6 mol / L, the EDTA concentration is 0.1-0.3 mol / L, and the copper ion concentration is 0.01-0.05 mol / L; the anodic oxidation time is 2-10 min; the anodic oxidation temperature is 30-50° C.; the anodic oxidation current density is 5-30 mA / cm 2 ;
[0033] The silane coupling agent used in the silane coupling agent treatment includes one or a combination of at least two of vinyl trichlorosilane, 3-aminopropyl triethoxysilane, vinyl triethoxysilane, vinyl tris(β-methoxyethoxy), γ-chloropropyl-trimethoxysilane or γ-methacryloxypropyl-trimethoxysilane; the mass concentration of the silane coupling agent in the treatment solution used in the silane coupling agent treatment is 10-15%; the temperature of the treatment solution used in the silane coupling agent treatment is 30-60°C; and the time of the silane coupling agent treatment is 10-15 minutes.
[0034] Compared with the prior art solutions, the present invention has the following beneficial effects:
[0035] During the surface treatment process of the present invention, the Cu2O+Cu(OH)2 surface is obtained after anodization and then coupled with a silane coupling agent so that the resulting copper foil has better transmission signal integrity. Under a 16 GHz signal, the signal loss after treatment by the present invention is significantly reduced compared with that after treatment with four commercially available browning solutions A, B, C, and D. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a SEM photograph of the surface of the copper foil obtained after anodization in Example 1 of the present invention;
[0037] Figure 2 It is a circuit diagram of signal loss detection in the present invention.
[0038] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims. DETAILED DESCRIPTION
[0039] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:
[0040] Example 1
[0041] This embodiment provides a method for processing the inner copper surface of a printed circuit board, which is as follows:
[0042] The copper foil is HTE copper foil. First, prepare the anodizing solution, which is composed of 7.5mol / L sodium hydroxide, 0.285mol / L potassium sodium tartrate, and 0.156mol / L EDTA. Add an appropriate amount of deionized water to a beaker, then add 60g sodium hydroxide, 16g potassium sodium tartrate tetrahydrate, and 6g EDTA. After dissolving, add deionized water to the 200mL scale line of the solution to obtain the anodizing solution. Then pickle, degrease, and ultrasonically clean the copper foil in turn to remove surface grease and impurities. Control the current to be constant at 9mA / cm at a temperature of 48°C.2 Oxidation for 3 min gave a Cu2O+Cu(OH)2 surface, such as Figure 1 As shown, the anodized copper foil was placed in an oven at 125°C for 3 minutes.
[0043] Then immerse the dried sample in a hydroalcoholic solution of a silane coupling agent (composed of 10wt% vinyltrichlorosilane, 10wt% H2O, 80wt% CH3CH2OH) at a temperature of 50°C. After soaking for ten minutes, take out the sample, rinse off the excess silane coupling agent on the surface with deionized water, and then put it in an oven for drying at 125°C for 3 minutes.
[0044] Then the treated copper foil, PP and substrate are pressed together, and the signal loss is tested after pressing together, as shown in Table 1.
[0045] Example 2
[0046] This embodiment provides a method for processing the inner copper surface of a printed circuit board, which is as follows:
[0047] The copper foil is HTE copper foil. First, prepare the anodizing solution, which is composed of 7.5mol / L sodium hydroxide, 0.285mol / L sodium ethylenediaminetetramethylenephosphate, and 0.156mol / L EDTA. Add an appropriate amount of deionized water to a beaker, then add 60g sodium hydroxide, 16g sodium ethylenediaminetetramethylenephosphate, and 6g EDTA. After dissolving, add deionized water to the 200mL scale line of the solution to obtain the anodizing solution. Then pickle, degrease, and ultrasonically clean the copper foil in turn to remove surface grease and impurities. Control the current to be constant at 12mA / cm at a temperature of 48°C. 2 Oxidation was performed for 5 min to obtain a Cu2O+Cu(OH)2 surface, and the anodized copper foil was placed in an oven at 125°C to dry for 3 min.
[0048] The dried samples were then immersed in a hydroalcoholic solution of a silane coupling agent (composed of 12 wt% 3-aminopropyltriethoxysilane, 10 wt% H2O, 78 wt% CH3CH2OH) at a temperature of 50°C. After soaking for ten minutes, the samples were taken out, the excess silane coupling agent on the surface was rinsed off with deionized water, and then placed in an oven for drying at 125°C for 3 minutes.
[0049] Then the treated copper foil, PP and substrate are pressed together, and the signal loss is tested after pressing together, as shown in Table 1.
[0050] Example 3
[0051] This embodiment provides a method for processing the inner copper surface of a printed circuit board, which is as follows:
[0052] The copper foil is HTE copper foil. First, prepare the anodizing solution, which is composed of 7.5mol / L sodium hydroxide, 0.285mol / L sodium tri-methylene phosphate, and 0.156mol / L EDTA. First, add an appropriate amount of deionized water to a beaker, then add 60g sodium hydroxide, 16g sodium tri-methylene phosphate, and 6g EDTA. After dissolving, add deionized water to the 200mL scale line of the solution to obtain the anodizing solution. Then pickle, degrease, and ultrasonically clean the copper foil in turn to remove surface grease and impurities. Control the current to be constant at 15mA / cm at a temperature of 45°C. 2 Oxidation was performed for 3 min to obtain a Cu2O+Cu(OH)2 surface, and the anodized copper foil was placed in an oven at 125°C to dry for 3 min.
[0053] The dried samples were then immersed in a hydroalcoholic solution of a silane coupling agent (composed of 15wt% vinyltriethoxysilane, 10wt% H2O, 75wt% CH3CH2OH) at a temperature of 50°C. After soaking for ten minutes, the samples were taken out, the excess silane coupling agent on the surface was rinsed off with deionized water, and then placed in an oven for drying at 125°C for 3 minutes.
[0054] Then the treated copper foil, PP and substrate are pressed together, and the signal loss is tested after pressing together, as shown in Table 1.
[0055] Example 4
[0056] This embodiment provides a method for processing the inner copper surface of a printed circuit board, which is as follows:
[0057] The copper foil is RTF copper foil. First, prepare the anodizing solution, which is composed of 7.5mol / L sodium hydroxide, 0.285mol / L sodium diethylenetriamine pentacarboxylate, and 0.156mol / L EDTA. First, add an appropriate amount of deionized water to a beaker, then add 60g sodium hydroxide, 16g sodium diethylenetriamine pentacarboxylate, and 6g EDTA. After dissolving, add deionized water to the 200mL scale line of the solution to obtain the anodizing solution. Then pickle, degrease, and ultrasonically clean the copper foil in turn to remove surface grease and impurities. Control the current to be constant at 15mA / cm at a temperature of 45°C. 2 Oxidation was performed for 1 min to obtain a Cu2O+Cu(OH)2 surface, and the anodized copper foil was placed in an oven at 125°C for 3 min.
[0058] The dried sample was then immersed in a hydroalcoholic solution of a silane coupling agent (composed of 11 wt% vinyl tri(β-methoxyethoxy), 10 wt% H2O, 79 wt% CH3CH2OH) at a temperature of 50°C. After soaking for ten minutes, the sample was taken out, the excess silane coupling agent on the surface was rinsed off with deionized water, and then placed in an oven for drying at 125°C for 3 min.
[0059] Then the treated copper foil, PP and substrate are pressed together, and the signal loss is tested after pressing together, as shown in Table 1.
[0060] Example 5
[0061] This embodiment provides a method for processing the inner copper surface of a printed circuit board, which is as follows:
[0062] The copper foil is RTF copper foil. First, prepare the anodizing solution, which is composed of 7.5mol / L sodium hydroxide, 0.285mol / L potassium sodium tartrate, and 0.156mol / L EDTA. First, add an appropriate amount of deionized water to the beaker, then add 60g sodium hydroxide, 16g potassium sodium tartrate tetrahydrate, and 6g EDTA. After dissolving, add deionized water to the 200mL scale line of the solution to obtain the anodizing solution. Then pickle, degrease, and ultrasonically clean the copper foil in turn to remove surface grease and impurities. Control the current to be constant at 15mA / cm at a temperature of 50°C. 2 Oxidation was performed for 2 min to obtain a Cu2O+Cu(OH)2 surface, and the anodized copper foil was placed in an oven at 125°C and dried for 3 min.
[0063] The dried samples were then immersed in a hydroalcoholic solution of a silane coupling agent (composed of 10 wt% γ-chloropropyl-trimethoxysilane, 15 wt% H2O, 75 wt% CH3CH2OH) at a temperature of 50°C. After soaking for ten minutes, the samples were taken out, the excess silane coupling agent on the surface was rinsed off with deionized water, and then placed in an oven for drying at 125°C for 3 minutes.
[0064] Then the treated copper foil, PP and substrate are pressed together, and the signal loss is tested after pressing together, as shown in Table 1.
[0065] Example 6
[0066] This embodiment provides a method for processing the inner copper surface of a printed circuit board, which is as follows:
[0067] The copper foil is RTF copper foil. First, prepare the anodizing solution, which is composed of 7.5mol / L sodium hydroxide, 0.285mol / L sodium ethylenediaminetetramethylenephosphate, and 0.156mol / L EDTA. First, add an appropriate amount of deionized water to a beaker, then add 60g sodium hydroxide, 16g sodium ethylenediaminetetramethylenephosphate, and 6g EDTA. After dissolving, add deionized water to the 200mL scale line of the solution to obtain the anodizing solution. Then pickle, degrease, and ultrasonically clean the copper foil in turn to remove surface grease and impurities. Control the current to be constant at 20mA / cm at a temperature of 50°C. 2Oxidation was performed for 2 min to obtain a Cu2O+Cu(OH)2 surface, and the anodized copper foil was placed in an oven at 125°C and dried for 3 min.
[0068] The dried samples were then immersed in a hydroalcoholic solution of a silane coupling agent (composed of 13wt% γ-methacryloxypropyl-trimethoxysilane, 12wt% H2O, 75wt% CH3CH2OH) at a temperature of 50°C. After soaking for ten minutes, the samples were taken out, the excess silane coupling agent on the surface was rinsed off with deionized water, and then placed in an oven for drying at 125°C for 3 minutes.
[0069] Then the treated copper foil, PP and substrate are pressed together, and the signal loss is tested after pressing together, as shown in Table 1.
[0070] Example 7
[0071] The copper foil is HVLP copper foil. First, prepare the anodizing solution, which is composed of 7.5mol / L sodium hydroxide, 0.285mol / L sodium diethylenetriamine pentacarboxylate, and 0.156mol / L EDTA. First, add an appropriate amount of deionized water to a beaker, then add 60g sodium hydroxide, 16g sodium diethylenetriamine pentacarboxylate, and 6g EDTA. After dissolving, add deionized water to the 200mL scale line of the solution to obtain the anodizing solution. Then pickle, degrease, and ultrasonically clean the copper foil in turn to remove surface grease and impurities. Control the current to be constant at 12mA / cm at a temperature of 50°C. 2 Oxidation was performed for 3 min to obtain a Cu2O+Cu(OH)2 surface, and the anodized copper foil was placed in an oven at 125°C to dry for 3 min.
[0072] The dried samples were then immersed in a hydroalcoholic solution of a silane coupling agent (composed of 10 wt% 3-aminopropyltriethoxysilane, 10 wt% H2O, 80 wt% CH3CH2OH) at a temperature of 50°C. After soaking for ten minutes, the samples were taken out, the excess silane coupling agent on the surface was rinsed off with deionized water, and then placed in an oven for drying at 125°C for 3 minutes.
[0073] Then the treated copper foil, PP and substrate are pressed together, and the signal loss is tested after pressing together, as shown in Table 1.
[0074] Example 8
[0075] In this embodiment, a commercially available A browning solution (Atotech (China) Chemical Co., Ltd.) was used to treat the copper foil surface. Then, the treated copper foil, PP and substrate were pressed together, and the signal loss was tested after pressing, as shown in Table 1.
[0076] Example 9
[0077] In this embodiment, a commercially available B brown chemical solution (Atotech (China) Chemical Co., Ltd.) was used to treat the copper foil surface. Then, the treated copper foil, PP and substrate were pressed together, and the signal loss was tested after pressing, as shown in Table 1.
[0078] Example 10
[0079] In this embodiment, a commercially available C browning solution (Unite Chemical Co., Ltd.) was used to treat the surface of the copper foil. Then, the treated copper foil, PP and substrate were pressed together, and the signal loss was tested after pressing, as shown in Table 1.
[0080] Embodiment 11
[0081] In this embodiment, a commercially available D browning solution (Unite Chemical Co., Ltd.) was used to treat the surface of the copper foil. Then, the treated copper foil, PP and substrate were pressed together, and the signal loss was tested after pressing, as shown in Table 1.
[0082] In the present invention, the signal loss detection in the above embodiment is performed according to the Delta-L method, and the test circuit is as follows: Figure 2 The copper foil, PP and substrate are pressed together by assembling the copper foil, PP and substrate in sequence.
[0083] Table 1
[0084]
[0085]
[0086] It can be seen from the results of the above embodiments that the surface treatment method provided by the present invention, by adopting a specific surface treatment process, enables the treated copper foil to avoid the problems of increased conductor loss in signal transmission and a significant impact on the integrity of high-frequency transmission signals, and significantly reduces the impact of conductor loss on signal integrity.
[0087] It is stated that the present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0088] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0089] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0090] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for treating the inner copper surface of a printed circuit board, It is characterized in that The processing method comprises: The copper foil is subjected to anodizing and silane coupling agent treatment in sequence; The current density of the anodic oxidation is 18-30 mA / cm 2 ; After anodization, the surface of the copper foil forms Cu 2 O and Cu(OH) 2 layer; The anodic oxidation liquid used in the anodic oxidation comprises sodium hydroxide, an organic acid salt, EDTA and copper ions; The sodium hydroxide concentration in the anodizing solution is 5-10 mol / L, the organic acid salt concentration is 0.1-0.6 mol / L, the EDTA concentration is 0.1-0.3 mol / L, and the copper ion concentration is 0.01-0.05 mol / L; The silane coupling agent used in the silane coupling agent treatment includes one or a combination of at least two of vinyl trichlorosilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy), γ-chloropropyl-trimethoxysilane or γ-methacryloxypropyl-trimethoxysilane; The mass concentration of the silane coupling agent in the treatment solution used in the silane coupling agent treatment is 10-15%; The temperature of the treatment liquid used in the silane coupling agent treatment is 30-60°C.
2. The processing method according to claim 1, It is characterized in that The anodizing time is 2-10 minutes.
3. The processing method according to claim 1, It is characterized in that The temperature of the anodizing is 30-50°C.
4. The processing method according to claim 1, It is characterized in that The silane coupling agent treatment time is 10-15 minutes.
5. The processing method according to claim 1, It is characterized in that The processing method comprises: The copper foil is subjected to anodizing and silane coupling agent treatment in sequence; After anodization, the surface of the copper foil forms Cu 2 O and Cu(OH) 2 layer; The anodic oxidation liquid used in the anodic oxidation comprises sodium hydroxide, organic acid salt, EDTA and copper ions; the sodium hydroxide concentration in the anodic oxidation liquid is 5-10 mol / L, the organic acid salt concentration is 0.1-0.6 mol / L, the EDTA concentration is 0.1-0.3 mol / L, and the copper ion concentration is 0.01-0.05 mol / L; the anodic oxidation time is 2-10 min; the anodic oxidation temperature is 30-50° C.; the anodic oxidation current density is 18-30 mA / cm 2 ; The silane coupling agent used in the silane coupling agent treatment includes one or a combination of at least two of vinyl trichlorosilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy), γ-chloropropyl-trimethoxysilane or γ-methacryloxypropyl-trimethoxysilane; the mass concentration of the silane coupling agent in the treatment solution used in the silane coupling agent treatment is 10-15%; the temperature of the treatment solution used in the silane coupling agent treatment is 30-60°C; and the time of the silane coupling agent treatment is 10-15 minutes.
